Information Technology Empowers Smart City Construction: Discussion Based on Smart City Solutions of Operators - Lijing Wu, Wenbo Wang, Ruyi Huang, Xiaohai Mu (Forest Chemicals Review, 1970)
Smart city is an advanced form of urban development that ADAPTS to the new social environment and meets the needs of citizens under the support of information Internet technology, based on the concept of open innovation, the integrated development of mobile technology and the democratization process of social development. The goal of smart city construction needs to make use of high-end technology and equipment and connectivity, and promote the refinement management level of cities through the construction of smart communities, smart parks, smart cities and other levels. In this process, enterprises will become the most important urban operation maintenance provider and the stable and lasting strategic partner of the government, and at the same time undertake corresponding social responsibilities.